Unidade de estudo para apoiar o ensino e aprendizagem de algoritmos e lógica de programação no ensino médio por meio do App Inventor - Pippi, Jonathan Donato (2023)
The National Common Curricular Base (BNCC), through a guiding document, determines guidelines that provide for the insertion of technologies in the teaching and learning process in Basic Education. Skills related to Computing awaken student autonomy, creativity and help in problem solving. There are already some national (CIEB and SBC) and international (CSTA K12) reference curricula in computing that disagree with the importance of teaching algorithms and programming logic in high school, as well as authors who suggest the use of technologies to support the teaching of this content. In this context, this work aims to develop a Study Unit to support the teaching and learning of algorithms and programming logic through the specific App Inventor for High School, verified according to the guidelines of reference curricula in computing. Based on the Instructional Design (ID) model known as ADDIE, activities related to teaching algorithms and programming logic are planned and educational resources are developed to support the execution of the Study Unit. This work was developed based on the Design Science Research (DSR) approach, which includes the development of an artifact to solve a problem in a given context. The results indicate that the App Inventor environment assists in the process of teaching and learning programming logic, and brings with it strategies that encourage users to solve problems, making them have more application and interest in application development. Based on the evaluation, it is possible to highlight that the UE “Learning Algorithms and LP through App Inventor” can contribute to fun learning, which enables engagement and motivation on the part of students during classes.